2011
DOI: 10.4149/av_2011_03_189
|View full text |Cite
|
Sign up to set email alerts
|

Heat-shock protein 70 is associated with the entry of Marek΄s disease virus into fibroblast

Abstract: Summary. -Literature pertaining to the interactions between Marek΄s disease virus (MDV) entry-related glycoproteins and corresponding receptors is still limited. Results from a Western blot analysis of cellular proteins for virus receptors and co-immunoprecipitation suggest that heat shock protein 70 (HSP70) is a potential cellular receptor for MDV glycoprotein gH. Plaque inhibition assays confirm the involvement of HSP70 in the early stages of MDV entry into chicken embryo fibroblasts (CEF). The present work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…The interaction between BmACE HSP70 is a 70 kDa housekeeping protein chaperone located on the cell surface of several prokaryotes and eukaryotes cells, and it is responsible for assuring nascent protein folding, refolding misfolded proteins, and facilitating protein transportation [36]. Research indicated that HSP70 contributes to the attachment and cell entry of multiple viruses such as rotavirus [21], dengue virus [37], Japanese encephalitis virus [38], Marek's disease virus [39], Hazara virus [40], Chikungunya virus [41], grass carp reovirus [42],…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction between BmACE HSP70 is a 70 kDa housekeeping protein chaperone located on the cell surface of several prokaryotes and eukaryotes cells, and it is responsible for assuring nascent protein folding, refolding misfolded proteins, and facilitating protein transportation [36]. Research indicated that HSP70 contributes to the attachment and cell entry of multiple viruses such as rotavirus [21], dengue virus [37], Japanese encephalitis virus [38], Marek's disease virus [39], Hazara virus [40], Chikungunya virus [41], grass carp reovirus [42],…”
Section: Discussionmentioning
confidence: 99%
“…HSP70 is a 70 kDa housekeeping protein chaperone located on the cell surface of several prokaryotes and eukaryotes cells, and it is responsible for assuring nascent protein folding, refolding misfolded proteins, and facilitating protein transportation [36]. Research indicated that HSP70 contributes to the attachment and cell entry of multiple viruses such as rotavirus [21], dengue virus [37], Japanese encephalitis virus [38], Marek’s disease virus [39], Hazara virus [40], Chikungunya virus [41], grass carp reovirus [42], Tembusu virus [43], enterovirus 71 [44], and echovirus 9 [45], in which HSP70 functioned as receptor, supplemental receptor, or accessory factor that facilitates viral binding to host cells and viral entry. Based on the findings of this study, we suggest that HSP70 of B. mori could be employed by DpCPV to facilitate viral attachment and cell entry.…”
Section: Discussionmentioning
confidence: 99%